A Universal DNA Aptamer that Recognizes Spike Proteins of Diverse SARS‐CoV‐2 Variants of Concern. Issue 15 (26th February 2022) - Zhang, Zijie; Li, Jiuxing; Gu, Jimmy; Amini, Ryan; Stacey, Hannah D.; Ang, Jann C.; White, Dawn; Filipe, Carlos D. M.; Mossman, Karen; Miller, Matthew S.; Salena, Bruno J.; Yamamura, Deborah; et al.
Abstract: Invited for the cover of this issue are John Brennan, Yingfu Li, and co‐workers at McMaster University. The image depicts MSA52 as a universal DNA aptamer that recognizes spike proteins of diverse SARS‐CoV‐2 variants of concern. Read the full text of the article at 10.1002/chem.202200078 . Abstract : " This study reports on a unique DNA aptamer, denoted MSA52, that displays a universally high affinity for the spike proteins of wildtype SARS‐CoV‐2 as well as the Alpha, Beta, Gamma, Epsilon, Kappa, Delta, and Omicron variants ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202200078 ).